An Integrated Approach to Healthier Livestock - Magnusson, Ulf (2021)
Presentation by Ulf Magnussen, livestock health flagship leader, on the herd health approach developed under the flagship. This presentation was delivered as part of the golden eggs session of the final celebration and closing meeting of the CGIAR Research Program on Livestock in Oct 2021.